Czech travelogues about Soviet Russia and the Soviet Union – a neglected source for historical geography - David, Jaroslav; Davidová GlogarováJana (Hungarian Geographical Bulletin, 2017)
This text focuses on Czech travelogues about Soviet Russia (and later the Soviet Union) dating from the period 1917–1968. The material – consisting of 72 published books – provides new insights into the historical perception of the Soviet Union. Most of the books represent the genre of ideological travel literature. They were written not only by journalists, writers and politicians, but also by members of professional delegations, e.g. firefighters, farmers, etc. The authors’ approach to the Soviet state changed during the period under investigation – from the initial desire (in the 1920s and 1930s) to uncover the secrets of the world’s first socialist state, to the uncritical admiration of the USSR that characterized the travelogues written during the 1950s, in line with official ideological dictates. This text explores the main tendencies that can be found in Czech travelogues about the Soviet Union, tracing how the treatment of key issues developed and changed over time, describing the strategies used by authors when presenting Soviet society and everyday life, and discussing the thematisation of proper names and the Russian language. Four issues of relevance to historical geography are examined: means of transport, itineraries, the depiction of nature, and the linguistic landscape.